Anti-lipogenic, anti-inflammatory, hepatic, and renal effects of Cardamom Essential Oil Loaded Nanostructured Lipid on Rats Fed High-Fat Diet - Saeed, Barzan Hasan Hama; Othman, Hemn Hassan; Ahmed, Basima Sadiq (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Cardamom has a variety of pharmacological properties. Objectives: This study examined the potential anti-lipogenic, anti-inflammatory, hepatic, and renal effects of Cardamom Essential Oil-Loaded Nanostructured Lipid Carrier (CEO-NLC) in rats fed high-lipid diets. Methodology: Male Sprague Dawley rats (No.= 42) were divided into 7 groups. The negative control group was fed standard normal rat chaw; the positive control group was fed a high-fat diet (HFD); the LCEO-NLC group was fed HFD and low doses of CEO-NLC, HCEO-NLC group fed HFD and high amount of CEO-NLC, atorvastatin group fed HFD with atorvastatin, atorvastatin/LCEO-NLC group fed HFD with atorvastatin in combination with LCEO-NLC, and CEO group fed HFD with CEO. All drenching processes were done for 14 consecutive weeks. The body weights were measured, and blood samples were taken to determine lipid profile, renal/hepatic enzymes, IL-1, IL-6, and TNF-α. Results: The LCEO-NLC, HCEO-NLC, atorvastatin, and atorvastatin/LCEO-NLC groups showed a lower body weight than the PC group (p<0.05). Compared with the PC group, the LCEO-NLC and other HFD groups significantly reduced serum cholesterol and triglyceride. Supplementation with LCEONLC decreases the ALP to 193.3 U/L vs 388.5 U/L in PC, while HCEO-NLC, atorvastatin and CEO groups recorded less improvement in ALP. The ALT and AST were significantly high (p<0.05) in the LCEO-NLC group when compared to NC or PC groups, and this increase was still high in the atorvastatin/LCEO-NLC group or in HCEO-NLC. The mean TSB was 0.125 mg/dl in the PC group, the mean was lower (0.117 mg/dl) in the LCEO-NLC group, and more decline was recorded (0.099 mg/dl) in the HCEO-NLC group. All study groups which received CEO-NLC did not show a significant change in urea/creatinine levels. The IL-1 and TNF-α were lowered in the LCEO-NLC group, while the HCEO-NLC group did not show a cytokine decline. Conclusions: CEO-NLC could control the rise in serum cholesterol and triglyceride but did not cause significant changes in renal function. Different doses of CEO-NLC had effects on liver enzymes and bilirubin. There were mild non-significant effects of atorvastatin on coadministration with CEO-NLC. Low concentrations of CEO-NLC cause reduce in the IL-1 and TNF-α but not IL-6.
Keywords: Nanoparticles; animalstudy; plant products; metabolic diseases